STATISTICS OF REGRESSION COEFFICIENT AND CORRELATION COEFFICIENT PRACTICAL ASSESSMENT OF SIGNIFICANCE - Shukurov Ikrom Abdurashitovich; Raximova Umida Ziyadullayevna; Egamkulov Davlatbek Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the social composition and structure of the labor resources of the population of the Republic of Uzbekistan. At the same time, we will provide scientifically sound proposals and considerations through practical, economic and econometric study and analysis of data such as the level of economic activity of the population, the share of permanent population of working age in relation to the total population, the level of employment and the unemployment rate.